2021
DOI: 10.2196/33739
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Perceptions, Intentions, and Uptake Among Young Adults in the United States: Prospective College-Based Cohort Study

Abstract: Background Uptake of the COVID-19 vaccine among US young adults, particularly those that belong to racial and ethnic minorities, remains low compared to their older peers. Understanding vaccine perceptions and their influence on vaccination uptake among this population remains crucial to achieving population herd immunity. Objective We sought to study perceptions of COVID-19 vaccines as well as intended and actual vaccine uptake among one population of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
2
16
1
2
Order By: Relevance
“…The parents' migratory situation, when at least one was born abroad but lives in Spain, was associated with vaccine hesitancy, a similar result was founded in a Canadian study [18]. Disparities in vaccination rates among students of different ethnicities was also demonstrated previously [15].…”
Section: Plos Onesupporting
confidence: 64%
See 1 more Smart Citation
“…The parents' migratory situation, when at least one was born abroad but lives in Spain, was associated with vaccine hesitancy, a similar result was founded in a Canadian study [18]. Disparities in vaccination rates among students of different ethnicities was also demonstrated previously [15].…”
Section: Plos Onesupporting
confidence: 64%
“…Epidemiological studies assessing determinants associated with the intention to vaccinate against SARS-CoV-2 may help to guide strategies for achieving the coverage that is necessary to avoid severity and mortality by COVID-19, and that could prevent the resurgence of this vaccine preventable disease [9,11,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about safety and efficacy have been shown to be a major barrier to vaccination across populations and countries [ 28 ]. Additional studies among college populations have also shown that a common reason for unwillingness to receive the vaccine are the belief that the vaccine approval process was rushed [ 15 ], as well as mistrust of the health care system or government held by Black individuals, as described earlier [ 29 ]. Our findings indicate that mistrust was also common among vaccinated BYA, suggesting the potential for other motivations to build trust and facilitate vaccine uptake, such as trusted sources to combat misinformation and inclusion of BYA in vaccination messaging and programs, given their potential as change agents.…”
Section: Discussionmentioning
confidence: 99%
“…Concern around vaccines is particularly salient in Black communities with deeply rooted medical mistrust due, in part, to well-known ethical violations, such as Henrietta Lacks and the Tuskegee study and structures, policies, and practices rooted in structural racism that create health inequities in many Black communities [10][11][12][13][14]. Several studies have identified that vaccine hesitancy varies by age and race, with Black communities having higher rates of vaccine hesitancy and younger age being associated with greater hesitancy across race/ethnicity [10,[15][16][17]. However, few studies focus specifically on BYA in the Southern United States who are an important population among which to increase vaccination, including both completion of the primary vaccine series and receipt of booster shots.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 cases in young adults, including college students, are more likely to be asymptomatic or paucisymptomatic carriers of SARS-CoV-2 compared to their older counterparts [ 2 ]. As the new variant spreads faster, if a case is not identified in time, the inevitable daily close contact may result in clustered epidemics and large-scale transmission [ 3 ].…”
Section: Introductionmentioning
confidence: 99%